Nutritional Status of Children Aged One Year in Urban and Rural Areas of North Karnataka – A Cross Sectional Study - Ashwini S; Katti, S M; Mallapur, M D (National Journal of Community Medicine, 2016)
Introduction: Exclusive breast feeding and appropriate complementary feeding practices are the most effective interventions to improve child health and prevent malnutrition. Methods: A cross-sectional study was done at urban and rural field practice areas of Department of Community Medicine, J. N. M. C., Belgaum. By random sampling, 380 rural mothers and 400 urban mothers having one year old child were selected. Information on socio-demographic variables, infant characteristics and infant feeding practices was collected from the mothers. Anthropometric measures of the infants were recorded. Results: Only 16.25% urban and 15.26% rural mothers had practiced exclusive breast feeding till 6 months of age. Complementary feeds were initiated by as many as 69.20% urban mothers before the infant was 6 months old. Minimum acceptable diet was given by 31.0% of the urban and 9.51% of the rural mothers. Wasting and stunting was more among rural than urban children. Conclusion: Nutritional status of urban infants is better than the rural infants. Various socio-demographic factors, infant characteristics and infant feeding practices were associated with the infants’ nutritional status.